2022
DOI: 10.1111/cns.13909
|View full text |Cite
|
Sign up to set email alerts
|

Elevated gamma‐glutamyl transferase levels are associated with stroke recurrence after acute ischemic stroke or transient ischemic attack

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…The study found that GGT elevation significantly increases the risk of gastrointestinal, lung, breast, gynecological, and hematological malignancies in cancer site-specific models (p<0.006). 26 A similar study involving men reported analogous results, linking elevated GGT levels to increased cancer risk, especially in men aged ≤65 years (p<0.001). 27 Furthermore, several studies have associated GGT elevation with poor prognosis in various malignancies, including pancreatic, cervical, prostate, and renal cancers.…”
Section: Discussionmentioning
confidence: 63%
“…The study found that GGT elevation significantly increases the risk of gastrointestinal, lung, breast, gynecological, and hematological malignancies in cancer site-specific models (p<0.006). 26 A similar study involving men reported analogous results, linking elevated GGT levels to increased cancer risk, especially in men aged ≤65 years (p<0.001). 27 Furthermore, several studies have associated GGT elevation with poor prognosis in various malignancies, including pancreatic, cervical, prostate, and renal cancers.…”
Section: Discussionmentioning
confidence: 63%
“…Baseline GGT level is positively and strongly associated with the risk for metabolic syndrome in a nonlinear dose-response manner [26,27]. Several epidemiologic studies have also demonstrated important advances in the definition of the associations between serum GGT level and the risk of overall mortality, coronary heart disease, type 2 DM, stroke, and chronic kidney disease [12,[28][29][30]. The regulatory mechanism of GGT expression has been already been widely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, GGT level is associated with a CVD diagnosis [9][10][11]. After a period of observation, researchers found that individuals with a higher GGT level were more likely than those with a lower GGT level to experience stroke [12,13]. Researchers also investigated the relationship between GGT level and adverse CVD clinical outcomes in stroke patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers also investigated the relationship between GGT level and adverse CVD clinical outcomes in stroke patients [14,15]. In addition, a previous study reported that an elevated GGT level is related to stroke recurrence and transient ischemic attack [13]. However, after adjusting for multiple factors, a previous study found that the association between GGT activity and stroke was no longer significant, suggesting that GGT activity might not be a good predictor of the severity of cardio-cerebrovascular diseases [16].…”
Section: Introductionmentioning
confidence: 99%